2019
DOI: 10.3390/pr7100759
|View full text |Cite
|
Sign up to set email alerts
|

Arsenic Removal from Mining Effluents Using Plant-Mediated, Green-Synthesized Iron Nanoparticles

Abstract: Arsenic contamination in industrial and mining effluents has always been a serious concern. Recently, nano-sized iron particles have been proven effective in sorptive removal of arsenic, because of their unique surface characteristics. In this study, green synthesis of iron nanoparticles was performed using a mixed extract of two plant species, namely Prangos ferulacea and Teucrium polium, for the specific purpose of arsenic (III) removal from the aqueous environment. Results of UV-visible spectrometry, X-ray … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(19 citation statements)
references
References 34 publications
1
18
0
Order By: Relevance
“…78 The intensity increase of two peaks at ≈2950 cm −1 was related to As–O bonds between OH − groups of the Fe-based active material and arsenic oxyanions. 79 A complete understanding of the adsorption mechanism for all the active materials was established with this information.…”
Section: Resultsmentioning
confidence: 99%
“…78 The intensity increase of two peaks at ≈2950 cm −1 was related to As–O bonds between OH − groups of the Fe-based active material and arsenic oxyanions. 79 A complete understanding of the adsorption mechanism for all the active materials was established with this information.…”
Section: Resultsmentioning
confidence: 99%
“…P. Karimi et al [153] biosynthesized iron nanoparticles from the leaf extracts of Prangos ferulacea and Teucrium polium and evaluated their arsenic adsorption capacity from the industrial effluent samples collected from two different mines. Studies showed that 93.9% arsenic was removed within 20 min from aqueous solutions at pH 6 and 2 g/L adsorbent dosage.…”
Section: Applicationsmentioning
confidence: 99%
“…Nano structure efficiency depends on the extraction method employed and their sources [9] . Nanoparticles can be synthesized within different time according to plant type and phytochemical concentration [10,11] and by using the various technics such as mechanical and chemical methods. Mechanical methods such as high-pressure homogenization (HPH), micro fluidization, ball milling, cryocrushing, high-intensity ultrasonication and chemical methods such as hydrolysis acid, 2,2,6,6-tetramethylpiperidine-1oxyl radical (TEMPO), periodate, and carboxymethylation.…”
Section: Introductionmentioning
confidence: 99%